Power structure: political process in American society - "Rose, Arnold M." (New York, 1967)
The influence of C. Wright Mills and Floyd Hunter, both on the general public and on academic researchers, has been startling, con sidering the usual reception given to sociological writings. Their con cepts of the "power elite" and the "power structure" apparently drew a gut reaction, and a great number of their readers from widely varied segments of the population-were prepared to believe their general theme that a relatively small economic elite controls the United States. The theme was not a new one, but Mills gave it an especially sophisticated formulation, Hunter backed it up with statistics, and both gave it an aura of sociological science. Although Hunter pub lished his Community Power Structure in 1953, and Mills published The Power Elite in 1956, the influence of these works is as strong today as it was a decade ago.
Keywords: Political Science